A Single-Institute Experience With Radioactive Seed Localization of Breast Lesions—A Retrospective Study. Issue 1 (February 2020) - Jumaa, Klaudia; Johani, Badria Al; Brackstone, Muriel; Kornecki, Anat
Objectives: To assess the benefits associated with radioactive seed localization (RSL) in comparison to conventional wire localization (WL) for nonpalpable breast lesions. Methods: Radioactive seed localization was initiated at our institution in July 2013. Retrospective review of all WL performed between June 2012 and July 2013 (2013) and all RSL performed during June 2015 and July 2016 (2016). Patients who received neoadjuvant therapy or did not undergo their planned surgeries and WL performed in 2016 were excluded. The following data were collected: final pathology, resection margins for malignant lesions, time to surgery, seed migration, and number of localized lumpectomies performed by each surgeon. Results: A total of 292 WL procedures (288 women) in 2013 and 194 RSL procedures (186 women) in 2016 were eligible for the study. All WLs were inserted the day of surgery. Mean time from RSL insertion to surgery was 4.0 ± 2.8 days (range: 1-17 days). There was no difference in specimen size for malignant lesions (6.8 ± 2.8 cm for WL and 6.9 ± 2.9 cm for RSL; P = .5). Specimen radiographs were obtained in 233 (80%) of 292 WL compared to 194 (100%) of 194 RSL ( P < .001). For malignant lesions, positive margins were present in 34 (17.2%) of 198 with WL compared to 15 (10.3%) of 146 with RSL ( P < .001). Close margins (≤1 mm) were present in 31 (15.6%) of 198 with WL compared to 1 (0.6%) of 146 with RSL ( P < .001). The seed fell out of the specimen during surgery in 6 (3.1%) of 194. No seed loss was recorded. The surgeons (n = 4) who transitioned to RSL increased the number of surgeries per month from a mean of 4.4 ± 2.6 in 2013 to 6.9 ± 3.5 in 2016, equivalent to a 41% increase ( P = .003). Conclusions: The use of RSL, as compared to conventional WL, resulted in a reduction in the number of pathologically involved surgical margins and was associated with an increased number of surgeries. Furthermore, RSL can be performed up to 14 days prior to surgery, which may improve scheduling flexibility in the radiology department.